Electronic id as an element of informatisation of health care - Perkowski, Bartosz (Studia Oeconomica Posnaniensia, 2013)
The article presents a potential of use of the electronic ID in e-Health systems. Replacement of the existing personal ID cards with electronic version creates opportunities not only for e-Government but also for other fields, such as medicine. The article details the usage of electronic ID cards in Belgium and Italy, and summarizes the activities carried out in Poland. The solutions used in medical healthcare in European countries and the current state of information systems used in the Polish healthcare are also discussed and the concept of computerization of the Polish health care using electronic patient record is presented. The summary of this article clarifies the requirements of e-Health systems that use electronic ID cards and specifies the benefits and drawbacks of such a solution.